2021
DOI: 10.5380/rbclima.v28i0.74717
|View full text |Cite
|
Sign up to set email alerts
|

Secas E Os Impactos Na Região Sul Do Brasil

Abstract: Embora eventos de secas sejam menos frequentes na Região Sul, se comparado com outras regiões do Brasil, quando ocorrem impactam o abastecimento de água, produção agrícola e a geração de energia elétrica. Portanto, a avaliação dos impactos da seca no setor agrícola e nos recursos hídricos, são de extrema importância para a gestão de riscos nesta região. Neste estudo avaliou-se os principais eventos de secas e seus impactos entre 1998 a 2020 (maio) na Região Sul do Brasil. Para isto, foram utilizados índices de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
(45 reference statements)
0
3
0
4
Order By: Relevance
“…Ocorreram apenas eventos de chuva isolados, que proporcionaram totais acumulados com valores, em alguns casos, significativos, porém, a distribuição temporal permaneceu irregular em todas as regiões do Estado (CARDOSO et al, 2020;JUNGES, 2020), o que pode ser verificado pelos valores de SPI negativos. Em grande escala, a atuação da ODP na sua fase fria ou negativa contribuiu para as anomalias negativas de precipitação no verão do RS (FERNANDES et al, 2021).…”
Section: Análise Dos Eventos De Secasunclassified
See 1 more Smart Citation
“…Ocorreram apenas eventos de chuva isolados, que proporcionaram totais acumulados com valores, em alguns casos, significativos, porém, a distribuição temporal permaneceu irregular em todas as regiões do Estado (CARDOSO et al, 2020;JUNGES, 2020), o que pode ser verificado pelos valores de SPI negativos. Em grande escala, a atuação da ODP na sua fase fria ou negativa contribuiu para as anomalias negativas de precipitação no verão do RS (FERNANDES et al, 2021).…”
Section: Análise Dos Eventos De Secasunclassified
“…Apesar disso, ressalta-se que a variabilidade interanual de precipitação na região afeta o rendimento da produção agrícola (BERLATO;FONTANA, 2003;CARDOSO et al, 2020;WREGE et al, 2012). Sistemas de grande escala influenciam o regime de precipitação na Região Sul do país, tais como o El Niño/Oscilação Sul (ENOS) (GRIMM et al, 1998(GRIMM et al, , 2000 e a Oscilação Decadal do Pacífico (ODP) (ANDREOLI; KAYANO, 2005;FERNANDES et al, 2021;SILVA, 2016). A diversidade de fenômenos que atuam na variação da precipitação do RS também influencia na intensidade, na distribuição e frequência da ocorrência de eventos extremos tais como períodos de estiagem ou enchentes (BRAZ et al, 2017).…”
Section: Introductionunclassified
“…Several drought events have also occurred in Amazonia, accentuating forest fires, affecting the region's biota, and signaling the risk of a tipping point [37][38][39][40][41][42][43]. Additionally, in the last decade, other Brazilian regions have also experienced severe droughts, such as the 2019/2020 droughts in the Brazilian Pantanal and Midwest [44][45][46] and the 2012/2013 and 2019/2020 droughts in southern Brazil [47,48]. Another South American region affected by droughts is Southeastern South America (SESA), which covers northern Argentina, Paraguay, Uruguay, and southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Brondani et al (2013), in a study about the occurrence of droughts and water supply problems in the municipality of Bagé, concluded that the city residents of Bagé have noticed the existence of drought in the municipality at least in the last 25 years, which has caused lack of water for public supply. According to Fernandes et al (2021), the 2019/2020 drought event occurred in the first quarter of 2020 with great intensity and expansion, as we can see through the impacts caused on the population in the municipality of Pelotas, during the summer of 2019/2020. The Santa Bárbara Dam, mainly responsible for supplying the municipality, reached the historical level of retreat, being 4,40 meters below the normal level since its construction (Diário Popular, 2021;Silveira, 2020).…”
Section: Introductionmentioning
confidence: 99%